Plasticisation Effect on Thermal, Dynamic Mechanical and Tensile Properties of Injection-Moulded Glass-Fibre/Polyamide 6,6 - Abd. Rahman, Nor Mas Mira; Hassan, Aziz; Yahya, Rosiyah (Journal of Science and Technology, 2011)
Polymer composites of polyamide 6,6 reinforced with short glass fibre were prepared by injection moulding, conditioned under dry, 50% relative humidity and wet. Investigations by TGA, DSC, DMA and tensile tests were conducted. TGA results revealed that glass fibre loading in PA 6,6 improve the thermal stability of the composites. DSC analysis revealed that the incorporation of glass fibre and moisture into the PA 6,6 matrix resulted in a remarkable decrease in the degree of crystallinity. DMA results revealed the glass transition temperatures are sensitive to moisture absorption and their values move to a lower temperature upon exposure to moisture. Incorporation of glass fibre into the polyamide 6,6 gives rise to a significant improvement in tensile modulus and tensile strength, while tensile strain is reduced. Exposure to different environments from dry to wet conditions resulted in a decrease in the strength and modulus, while tensile strains decrease.